2022
DOI: 10.1371/journal.pgph.0000628
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Covid-19 pandemic on the uptake of routine maternal and infant vaccines globally: A systematic review

Abstract: Maintaining routine vaccination coverage is essential to avoid outbreaks of vaccine-preventable diseases. We aimed to understand the international impact of the COVID-19 pandemic on routine vaccination in pregnant women and children aged 0-5-years-old. A systematic review of quantitative and mixed methods studies exploring changes in vaccination coverage, vaccination services, and vaccine confidence since the start of the Covid-19 pandemic was conducted. MEDLINE, EMBASE, CINHAL, PsychINFO, Web of Science, Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 46 publications
4
13
0
1
Order By: Relevance
“…The impact of the COVID-19 pandemic on immunization coverage remains to be seen although our data suggest it has affected attitudes about, and access to, the HPV vaccine. Many countries saw disruptions to vaccination programs, including HPV vaccination, particularly early in the pandemic, although these disruptions varied greatly in extent, duration, and mitigation [38] , [39] , [40] , [41] , [42] , [43] . We urgently need more data about how the pandemic has affected attitudes about, access to, and norms around vaccines, particularly non-routine vaccination like the HPV vaccine, which may face different barriers than childhood vaccines due to its timing and setting.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the COVID-19 pandemic on immunization coverage remains to be seen although our data suggest it has affected attitudes about, and access to, the HPV vaccine. Many countries saw disruptions to vaccination programs, including HPV vaccination, particularly early in the pandemic, although these disruptions varied greatly in extent, duration, and mitigation [38] , [39] , [40] , [41] , [42] , [43] . We urgently need more data about how the pandemic has affected attitudes about, access to, and norms around vaccines, particularly non-routine vaccination like the HPV vaccine, which may face different barriers than childhood vaccines due to its timing and setting.…”
Section: Discussionmentioning
confidence: 99%
“…trending. 43,44 The full consequences for missed in-person, well-child visits and decreased routine vaccination rates and the potential future impact on pediatric emergency care are yet unknown.…”
Section: Impact On Pediatric Outpatient Carementioning
confidence: 99%
“…The effect of these missed in‐person appointments for children may be far reaching, including delays in diagnoses that have significant impact on a child's life, as well as susceptibility to disease that may lead to downstream infections and future morbidity and mortality 42 . Additionally, since the start of the pandemic, routine immunization rates in the United States and globally have been down trending 43,44 . The full consequences for missed in‐person, well‐child visits and decreased routine vaccination rates and the potential future impact on pediatric emergency care are yet unknown.…”
Section: Ed and Healthcare System Operationsmentioning
confidence: 99%
“…It is now widely recognised that routine immunisation (RI) was disrupted globally during the start of the COVID-19 pandemic and throughout 2020 [1][2][3][4]. Single-country studies, and literature reviews have reported delays and interruptions in service delivery, decreases in attendance, and/or full suspension of services during the pandemic, e.g., during periods of quarantine or implementation other nonpharmaceutical interventions.…”
Section: Introductionmentioning
confidence: 99%